Evaluation of students’ engagement and motivation to participate in virtual events / Sheikh Ali Azzran Sh Said ... [et al.] - Sh Said, Sheikh Ali Azzran; Mohd Yussof, Farrah Norizzah; Sahamir, Shaza Rina; Yunos, Julitta; Mohamed, Mohd Afzan @ Noorawavi (UiTM Press, 2025)
The swift change of physical to online classes has significantly changed the educational landscape in the era of the new normal. The use of the Internet for online learning has soared significantly, and students are highly dependent on it by intensively and regularly attending classes. The development of online learning offers opportunities not only academic but also extracurricular activities such as virtual events to enhance students’ engagement and motivation in the online learning environment. By using electronic communication such as Google Meet and WhatsApp, students are able to interact and demonstrate their skills, knowledge and confidence in virtual events regardless of their geographical location. Consequently, students are able to feel motivated and engaged with other students and, thus, build up their morale to participate in virtual events. The purpose of this research is to explore the characteristics of students’ engagement and motivation across years of study and gender as factors affecting their participation in virtual student events. The Motivation and Engagement Scale (MES) was adapted, and quantitative analysis of descriptive statistics and an independent t-test were carried out. A simple random sampling of 122 undergraduate students from the construction management course completed the questionnaire. The findings show that overall, students are highly engaged and motivated to participate in virtual events. The research also revealed the underlying key factors of students’ engagement and motivation. The contribution of this research reveals that the transition to online learning, including virtual events facilitated by tools like Google Meet and WhatsApp, significantly enhances student engagement and motivation, providing key insights for improving online educational experiences.